Identifying crosstalk genetic biomarkers linking a neurodegenerative disease, Parkinson’s disease, and periodontitis using integrated bioinformatics analyses - Hu, Shaonan; Li, Simin; Ning, Wanchen; Huang, Xiuhong; Liu, Xiangqiong; Deng, Yupei; Franceschi, Debora; Ogbuehi, Anthony Chukwunonso; Lethaus, Bernd; Savkovic, Vuk; Li, Hanluo; Gaus, Sebastian; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: To identify the genetic linkage mechanisms underlying Parkinson’s disease and periodontitis, and explore the role of immunology in the crosstalk between both these diseases. Methods: The Gene Expression Omnibus (GEO) datasets associated with whole blood tissue of Parkinson’s disease patients and gingival tissue of periodontitis patients were obtained. Then, differential expression analysis was performed to identify the differentially expressed genes (DEGs) deregulated in both diseases, which were defined as crosstalk genes. Inflammatory response-related genes (IRRGs) were downloaded from the MSigDB database and used for dividing case samples of both diseases into different clusters using k-means cluster analysis. Feature selection was performed using the LASSO model. Thus, the hub crosstalk genes were identified. Next, the crosstalk IRRGs were selected and Pearson correlation coefficient analysis was applied to investigate the correlation between hub crosstalk genes and hub IRRGs. Additionally, immune infiltration analysis was performed to examine the enrichment of immune cells in both diseases. The correlation between hub crosstalk genes and highly enriched immune cells was also investigated. Results: Overall, 37 crosstalk genes were found to be overlapping between the Parkinson’s disease-associated DEGs and periodontitis-associated DEGs. Using clustering analysis, the most optimal clustering effects were obtained for periodontitis and Parkinson’s disease when k=2 and k=3, respectively. Using the LASSO feature selection, five hub crosstalk genes, namely, FMNL1, MANSC1, PLAUR, RNASE6, and TCIRG1, were identified. In periodontitis, MANSC1 was negatively correlated and the other four hub crosstalk genes (FMNL1, PLAUR, RNASE6, and TCIRG1) were positively correlated with five hub IRRGs, namely, AQP9, C5AR1, CD14, CSF3R, and PLAUR. In Parkinson’s disease, all five hub crosstalk genes were positively correlated with all five hub IRRGs. Additionally, RNASE6 was highly correlated with myeloid-derived suppressor cells (MDSCs) in periodontitis, and MANSC1 was highly correlated with plasmacytoid dendritic cells in Parkinson’s disease. Conclusion: Five genes (i.e., FMNL1, MANSC1, PLAUR, RNASE6, and TCIRG1) were identified as crosstalk biomarkers linking Parkinson’s disease and periodontitis. The significant correlation between these crosstalk genes and immune cells strongly suggests the involvement of immunology in linking both diseases. Keywords: Neurodegenerative disease, Parkinson’s disease, periodontitis, crosstalk genes, bioinformatics.